Effect of olive oil and sesame oil on some biochemical parameters in local male rabbits induced with diabetes - Shahad N. Al_azawi; Zaid M. Mubark Al_mahdawi (Tikrit Journal of Pure Science)
This study was designed to investigate the effects and protective role of olive and sesame oil in the level of cholesterol, triglyceride, albumin, urea and glutathione in the blood of males rabbits which induced with diabetes by of Aloxan . The study was achieved in the Animal House of the Faculty of Veterinary Medicine\ University of Tikrit. The experiment included 20 local rabbits divided randomly into four groups: the first control group was treated with a 0.9% physiologic solution. The second group was treated with Aloxan at a concentration of 150 mg / kg. The third group was treated with Aloxan and olive oil at a concentration of 1.25 ml / kg. The fourth group was treated with Aloxan and sesame oil at a concentration of 0.5 ml / kg. The experiment lasted for 30 days then the animals were sacrifice and the serum kept for biochemical tests. The results showed that there was a significant increase (P ≤ 0.05) in the concentration of cholesterol and a significant decrease in concentration of triglycerides, albumin, urea and glutathione